The Impact of Trade on Employment, Welfare, and Income Distribution in Unionized General Oligopolistic Equilibrium - Hartmut Egger; Daniel Etzel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2010)
This paper sets up a general oligopolistic equilibrium model with unionized labor markets. By accounting for productivity differences, the model features pro t and wage differentials across industries. We use this setting to study the impact of trade liberalization on employment, welfare, and the distribution of income. In particular, we show that a movement from autarky to free trade with a symmetric partner country lowers union wage claims and therefore stimulates employment and raises welfare. Whether rms can extract a larger share of rents in the open economy depends on the competitive environment as well as on the degree of centralization in union wage setting. Finally, the distribution of proft income across firm owners remains unaffected, while the distribution of wage income becomes more equal when a country opens up to trade.
Keywords: F12; F16; J51; L13; 330; General oligopolistic equilibrium; Unionized labor market; Trade liberalization; Income distribution; Außenhandelsliberalisierung; Beschäftigungseffekt; Verteilungswirkung; Wohlfahrtsanalyse; Oligopol; Allgemeines Gleichgewicht; Gewerkschaftsmitgliedschaft; Lohnverhandlungen; Mehr-Sektoren-Modell; Produktivität; Lohnstruktur; Theorie